MYTH AND HISTORICAL REALITY IN TOPONYMIC LEGENDS: MUTUAL RELATIONSHIPS - Zeynalova, Zuleykha (SWorldJournal, 2025)
The article is devoted to the study of the mythological sources of Azerbaijani toponymic legends and their mutual relations with historical reality. The main goal is to reveal how legends play a bridge role between myth and history in the folk memory. The